Evaluation of the application of inhalation anaesthesia and TIVA from economical perspectives - Erhan, O.L.; Yasar, M.A.; Onal, S.A.; Ugur, F.; Abdulhayoglu, B.; Bestas, A. (My University, 1994)
Halogenated compounds are widely used in contemporary anaesthesia applications. Local and systemic side effects and even mortality associated with the utilization of halogenated compounds have prompted researches to look for new techniques in anaesthesiology. Another unwanted aspect of halogenated compounds is that these drugs are expensive. In this report, economical considerations regarding inhalation anaesthesia and TIVA application are compared. In 82 patients out of 161 patients (ASA I-II, 7-68 age) inhalation anaesthesia (halothane, enflurane, isoflurane) and in 79 patients, TIVA (propofol - 50 ?g/kg/min in the first 30 min and later 33 ?g/kg/min doses) were utilized. In all the cases where O2, N2O and muscular relaxants were applied, anaesthetic spendings were calculated. Inhalational anaesthetic, made up 37.99 % of overall expenditures in inhalation group whereas in TIVA and isoflurane group, these rates were 54.24 % for propofol and 61.69 % for isoflurane respectively. Anaesthesiologists prefer isoflurane for ecological considerations and in cases where the patient has hepatotoxic injury. However, isoflurane is an expensive anaesthetic drug and this point should be evaluated carefully before drug selection in our country. Our results indicate that TIVA application is less expensive method of anaesthesia as compared to isoflurane. But it is a more expensive choice if compared to halothane. Thus, the selection of anaesthetic agent should be made regarding the clinical situation of the patients in this respect.
Keywords: Economy in anaesthesia; General anaesthesia; TIVA